Evaluating the Potential and Limits of Green Electrolysis in Future Energy Scenarios with High Renewable Share - Angelica Liponi; Gianluca Pasini; Andrea Baccioli; Lorenzo Ferrari (Energies)
Water electrolysis is a potential contributor to global decarbonization, enhancing the flexibility and resilience of the electricity system and enabling integration with different sectors, such as industry and transportation, by acting as an energy vector and storage, as well as chemical feedstock. This study investigates the potential of hydrogen production by electrolysis in future national electric grid scenarios for Italy as a case study. It examines the impact of increasing photovoltaic and wind capacities up to five times the 2019 levels, considering an electricity storage capacity of up to 200 GWh. The feasibility of fully meeting current national hydrogen consumption through electrolysis in these scenarios is assessed by considering different overall electrolysis capacities. Specific CO2 emissions associated with hydrogen production are evaluated as an indicator of environmental feasibility and compared with the conventional steam methane reforming. In addition, the levelized cost of hydrogen production is evaluated as an indicator of economic feasibility. Some limitations of electrolysis emerge when it is considered the sole way to decarbonize hydrogen production. Very high renewable shares are required to make electrolysis alone a feasible solution. Aiming to maximize the use of renewable curtailment for electrolysis conflicts with maximizing the electrolyzers’ utilization factor, thus, negatively affecting hydrogen production costs. Furthermore, since priority is given to the use of renewable and stored electricity to meet electricity demand, the remaining electricity is insufficient to produce the entire hydrogen demand in most of the considered scenarios, particularly when substantial storage supports the grid, as this reduces the curtailment available for electrolysis.